Save the Generation and the World of Young People by Stop Smoking in Hamlet 4 Pekik Nyaring Village, Pondok Kelapa Sub-District, Bengkulu Tengah Regency - Riana, Adhe Okta; Gustiana , Sika Mana; Wahyuni, Triana Sri; Putri, Yesi; Sudiyanto (Jurnal Pengabdian Mandiri, 2024)
ISPA disease is a common illness among children and teenagers due to their still developing immune system. Cigarettes are one of the addictive substances that can cause health hazards for oneself and society if used. Therefore, various anti-smoking activities are needed for health. Smoking is an activity done by an individual by burning or inhaling a cigarette, which can cause the smoke to be inhaled by everyone around them. Smoking has harmful effects. This is not only harmful to the health of the smoker but also to the health of those nearby. The education on the dangers of smoking for elementary school children and teenagers is crucial to increase their awareness and ability to face various challenges they encounter. This activity aims to provide accurate and clear information about the dangers of smoking and increase the ability of children and teenagers to face various situations related to smoking. This educational activity is carried out using PowerPoint and leaflets about the dangers of smoking. The results of this educational activity show that the knowledge of children increased from 33% to 89%, while that of teenagers increased from 40% to 60%. A significant increase was observed in their knowledge and awareness about the negative impact on health.